Dating the Mizuho 700-m core from core ice fabric data - Nakawo,Masayoshi; Ohmae,Hirokazu; Nishio,Fumihiko; Kawada,Takao (National Institute of Polar Research, 1989)
P(論文) The vertical strain rate of the ice sheet has been estimated from the longitudinal total strain derived from Mizuho core fabric data. The vertical strain rate is considered to be the average value in the past while the ice sheet has experienced a significant thinning. With use of the obtained vertical strain rate, the age of ice in the Mizuho core has been dated. It was shown that the 700-m core corresponds with the time period of the past 9400 years. departmental bulletin paper